Pengembangan Media Pembelajaran Berbasis Android melalui Model Pembelajaran PAIKEM (Pembelajaran Aktif, Inovatif, Kreatif, dan Menyenangkan) - Annisa Utama Berliana; Mailizar Mailizar; Faiza Faiza; Leonard Leonard (EduResearch Mitra Inovasi, 2021)
The objective of the research is to develop android-based mathematics learning media on mathematics materials of junior high school class VIII quality to be used in the learning process. The research model used to develop this media is the learning model of ADDIE (Analysis, Design, Development, Implementation, Evaluation). In this study, the media were trialled to one material expert, one media expert, one development specialist, 3 students with different skill levels and twenty-two students on a field trial. From the results of these tests obtained the conclusion that this android-based mathematics learning media can be categorized